Versailles, the visit - Saule, Beatrix; Corbiau, Gérard; Petitgirard, Laurent (Public Media, 2002)
Visit the world's most famous chateau in the heart of Versailles. Discover the palace, the park, and the gardens through a circut arranged chronologically and by subject matter. Certain areas generally closed to the public are shown as well.